2017
DOI: 10.1177/0010414017710265
|View full text |Cite
|
Sign up to set email alerts
|

The Autocratic Welfare State: Old-Age Pensions, Credible Commitments, and Regime Survival

Abstract: In this paper we argue that autocratic regimes are no less likely than democracies to adopt old-age pensions, although autocratic programs are less universal in their coverage. Our theoretical argument focuses on the strong incentives that autocratic regimes have for enacting and maintaining such programs to ensure regime survival. Autocratic pension programs can be considered club goods that I) are targeted to critical supporting groups and II) solve credible commitment problems on promises of future distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 75 publications
(104 reference statements)
4
58
1
1
Order By: Relevance
“…Usually the small circle of supporters includes organized groups with identifiable features, eg. ruling party members, soldiers, landowners, civil servants, teachers, industrial workers or business groups (Knutsen & Rasmussen, 2018). Because retracting the support from these groups can increase the chance of regime collapse or leadership change, a wide range of private goods tend to be provided to them.…”
Section: Left Versus Right On Particularistic Benefitsmentioning
confidence: 99%
“…Usually the small circle of supporters includes organized groups with identifiable features, eg. ruling party members, soldiers, landowners, civil servants, teachers, industrial workers or business groups (Knutsen & Rasmussen, 2018). Because retracting the support from these groups can increase the chance of regime collapse or leadership change, a wide range of private goods tend to be provided to them.…”
Section: Left Versus Right On Particularistic Benefitsmentioning
confidence: 99%
“…Later experiences have provided support for the same conclusion (Besley and Kudamatsu, 2006;Haggard and Kaufman, 2008;Kudamatsu, 2012;Lindert, 2004). However, a deviant idea has recently been presented -and substantiated -by Knutsen and Rasmussen (2018). Looking particularly at old-age pensions, they found that such schemes are as likely to be introduced in nondemocracies; the rationale being that such endeavours increase the probability of regime survival.…”
Section: Social Protectionmentioning
confidence: 99%
“…Its correlation with our measure was 0.64. In addition, Knutsen and Rasmussen's (2018) data include an index of the overall degree of universalism in the six programmes considered, for approximately half of the observations in our longitudinal dataset. The correlation between this index and our indicator of SP was 0.87.…”
Section: Measurements and Datamentioning
confidence: 99%
“…If liberalization of the regime is a very undesirable outcome for incumbents, they may be willing to pursue rather expensive policies to co-opt or appease opposition both within their ruling coalition and the general public. Examples of such policies could include investments in various local or national public goods, but targeted pension programs (Knutsen and Rasmussen, 2018) is one type of redistributive policy that is often introduced or expanded in order to co-opt specific groups in non-democratic regimes. Thus, one potential explanation for the lack of an observed correlation between economic crises and incumbent-guided liberalizing transitions is that incumbent elites might fend off threats spurred by a crisis by pursuing particular, redistributive policies, without overseeing a liberalization of the regime.…”
Section: Disaggregating Regime Change From Withinmentioning
confidence: 99%